Formal institutions, ICSID arbitration and firm performance: evidence from Latin America - Enriquez-Perales, Sarela; Garcia-Gomez, Conrado Diego; Díez-Estaban, José María; Lizarzaburu Bolaños, Edmundo R. (Springer, 2022)
This paper analyzes how a country’s formal institutional quality impacts the performance of listed companies across different Latin American countries (namely, Argentina, Brazil, Colombia, Mexico, Peru, and Chile) and industries. Latin America provides a unique setting to address this question due to the region’s high institutional instability. The sample consists of 571 large listed companies, with a total of 8576 observations, for the period 2004–2019. Results show that the quality of a country’s formal institutions is positively related to firm performance, measured through two alternative variables (ROA and Tobin’s Q). Additionally, countries that are signatories of the ICSID agreement provide companies with a more stable environment in which to do business, which ultimately has a positive impact on their performance. However, as the number of cases recorded before the ICSID increases, the relationship turns negative. The paper provides a more comprehensive understanding of formal institutions by considering six alternative governance dimensions. Moreover, international arbitration is found to be a substitute for formal institutions in Latin American countries.
Keywords: Formal institutions; ICSID; Instituciones formales; Arbitration; CIADI; Firm performance; Arbitraje; Desempeño de la firma; Latin America; América Latina; https://purl.org/pe-repo/ocde/ford#5.02.04